Comparative Analysis of the Morphological, Physiological, Proteomic, and Metabolic Mechanisms of the “Biloxi” Blueberry Response to Shade Stress - Wu, Yaqiong; Huang, Zhengjin; Zhang, Chunhong; Shi, Chong; Lyu, Lianfei; Li, Weilin; Wu, Wenlong (Frontiers in Plant Science, 2022)
Blueberry is an important small berry crop in economic forests. In hot summers, the top tip of blueberry often burns and withers due to water loss. Therefore, this study subjected blueberry to shading treatment in the summer to study the effects of different shading treatments on the growth, morphology, physiology and protein levels of the plant. The results showed that the 50% shading (T1) treatment yielded the highest average increases in plant height, crown width and ground diameter of blueberry. Under the 80% shading (T2) treatment, the cells of the leaves dissolved, the morphology was incomplete, the vascular bundles disappeared, and no supporting skeleton was detected. As demonstrated by physiological and biochemical data and the proteome expression levels, the T1 shading treatment was beneficial to the growth of blueberry and significantly enriched the photosynthetic pathway and flavonoid biosynthesis. An analysis of the interaction network of differentially expressed proteins indicated that trans-cinnamate 4-monooxygenase (C4H, CYP73A), naringenin 3-dioxygenase (F3H) and bifunctional dihydroflavonol 4-reductase/flavanone 4-reductase (DFR) exhibited high connectivity and mutual regulation. In short, 50% shading can improve the growth index of blueberry and lead to an enrichment of flavonoid biosynthesis. This study provides a scientific basis for the breeding and summer protection of blueberry seedlings.